The Empowerment Of Role Of The Family In Developing Character Of Environmental Awareness In Elementary School-Age Children - Kadek Aria Prima Dewi PF (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2017)
This research aims to see the empowerment process of role of the family through Waste Bank media to develop character of environmental awareness in elementary school-age children. The qualitative descriptive research methodology is used. The result of this research shows that the empowerment of role of the family in developing character of environmental awareness in elementary school-age children in State Elementary School 1 Padangsambian is determined by the role of waste bank media through intervention of school to students' parents. The initial stage of intervention activity is performed with parenting activity in school with the theme of environmental awareness. Furthermore, all forms of activities or moral actions of environmental awareness are guided by Waste Bank community. The family becomes active in the environmental awareness activity and the control process is implemented together by school and Waste Bank community.